PEMAHAMAN MASYARAKAT KAMPUNG LAMA TERHADAP PEMAKAIAN GELANG HITAM PADA BAYI PERSPEKTIF AL-QUR’AN - Lia Simanjuntak (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2023)
This article will explore a study of the living Koran, which is related to the understanding of the people of Kampung Lama about the use of bracelets made of black thread to be worn on a newborn to the age of 1 year. It is usually applied by the community as part of a custom or tradition to use a black thread bracelet that recites verses from the Koran on the hands and feet of a baby. This cannot be separated from their belief in the miracles of the Koran which they believe is a barrier from interference by jinns or spirits that will disturb them. This study aims to describe how people's understanding regarding the use of black bracelets on a baby. This type of research is field research or field research. The research instrument is observation, interview guidelines. The source of this research data is the results of interviews obtained from the people who are the respondents of this study. The results of this study are related to people's understanding of the use of black bracelets for various reasons. Among them, there are those who believe that wearing black bracelets is one of the efforts to prevent children from being disturbed by spirits. There are also those who just follow their parents' orders, because they are afraid that something will happen to the baby.